Similar Trajectories in Current Alcohol Consumption and Tick-Borne Diseases: Only Parallel Changes in Time or Links Between? - Frątczak, Martyna; Petko, Branislav; Sliwowska, Joanna H.; Szeptycki, Jan; Tryjanowski, Piotr (Frontiers in Cellular and Infection Microbiology, 2021)
In a modern world, both tick-borne diseases and alcohol consumption are among major public health threats. In the present opinion article, we pose the question, whether these two health problems: alcohol consumption and tick-borne diseases prevalence can be related. We hypothesize that it is possible due to at least three factors: outdoor places chosen for alcohol consumption, behavioural changes induced by alcohol, and possible stronger attraction of human hosts after alcohol consumption to ticks. Many important clues are coming from social studies about people’s preference of places to consume alcohol and from studies regarding the attraction of people consuming alcohol to mosquitos. These data, however, cannot be directly transferred to the case of alcohol consumption and ticks. Therefore, we suggest that more detailed studies are needed to better understand the possible individual attractiveness of people to ticks and ways alcohol may influence it.